The importance of the skills in business digitalization for the internationalization strategy: Evidence for Portuguese firms - Lobo, Carla Azevedo (2020)
To meet the requirements of both national and international competition firms need to engage in a continuous innovation process and constantly restructure their operations. Firms must find new ways to develop a competitive advantage, which entails searching for and acquiring new skills, resources and competences. Traditional theories of internationalization focused mainly on multinational firms, giving less importance to entrepreneurs with their small businesses. However, the development of the business world has been breaking all boundaries with the increasing internationalization of firms, not dependent on their size, activity sector or geographical area of origin. It is also widely acknowledged that organizations have suffered a large evolution at the technological level where the traditional barriers of information and knowledge transferring have been progressively eliminated. Digital transformation (DT), in business practice can enable significant competitive advantage. DT can also be seen as a deep and accelerating transformation with regard to processes, activities, competences and models, in order to take advantage of the changes and opportunities offered by the inclusion of digital technologies into an organization. In the literature of business internationalization, a large number of scientific studies focus on the determinants of internationalization and more specifically, on their relationship with the success / failure of internationalization. However, few of them analyze the entrepreneur’s perspective. Therefore, this work aims to present a study focused on the entrepreneur’s perception about the internationalization process of his company, more specifically, about the factors that enhanced the company entry into foreign markets as well as the constraints found in this process. In this project, through an empirical study from a sample of 195 Portuguese International firms, we intend to confirm if the integration of technological innovations in business practice can enable significant competitive advantage including in business internationalization.